Exploring the Effects of Artemisia absinthium L. Essential Oil on Pseudopregnancy Model in Rats - Demirel, Murside Ayse; Suntar, Ipek; Ceribasi, Ali Osman; Taban, Kevser; Zengin, Gokhan (Wiley, 2025)
Pseudopregnancy is a luteal phase syndrome characterized by symptoms of late pregnancy and/or early postpartum periods. This phenomenon is observed in various species, including rats, rabbits and dogs, and arises due to hormonal alterations. Due to the significant side effects of current treatment regimens, there is a growing need for the development of alternative therapeutic strategies. In this context, various plants and natural compounds have been investigated for their potential to modulate hormonal balance, offering a promising avenue for the treatment of pseudopregnancy. Artemisia absinthium L., a medicinal plant traditionally utilized as an emmenagogue and abortifacient, is known for its regulatory effect on the dopaminergic system. The study aimed to assess whether A. absinthium treatment could restore oestrous cyclicity in pseudopregnant rats. Pseudopregnancy was induced through the administration of a pregnant mare's serum gonadotropin and human chorionic gonadotropin in female rats. The essential oil of A. absinthium was administered orally at doses of 12.5, 25 and 50 mg/kg once daily for 10 days, with bromocriptine as a reference treatment. The results indicated that the 25 mg/kg dose of A. absinthium essential oil exhibited beneficial effects in the pseudopregnancy model. Gas chromatography analysis revealed that the major components of the essential oil included cis-chrysanthenyl acetate (17.8%), sabinyl acetate (11.6%), terpinen-4-ol (6.2%), caryophyllene oxide (5.5%) and (E)-nuciferol (5.5%). These findings suggest that A. absinthium essential oil may present a promising therapeutic option for the management of pseudopregnancy.
Keywords: Artemisia absinthium; Asteraceae; essential oil; in vivo; pseudopregnancy